Human papillomavirus genotype affects metastatic rate following radiotherapy in patients with uterine cervical cancer - Okonogi, Noriyuki; Kobayashi, Daijiro; Suga, Tomo; Imai, Takashi; Wakatsuki, Masaru; Ohno, Tatsuya; Kato, Shingo; Nakano, Takashi; Kamada, Tadashi (Oncology letters, 2018)
Human papillomavirus (HPV) infection is well known as a major etiological risk factor associated with carcinogenesis in uterine cervical cancer. However, few reports have investigated the association between HPV genotype and outcome in patients with uterine cervical cancer following radiotherapy (RT). The aim of the present study was to investigate the association between the HPV genotype and clinical outcome following RT in Japanese patients with uterine cervical cancer. Between November 2001 and August 2006, 157 Japanese women with uterine cervical cancer were treated with RT or concurrent chemoradiotherapy with curative intent. Pretreatment, formalin-fixed, paraffin-embedded biopsies were obtained from 83 patients. HPV genotypes were determined using the polymerase chain reaction method. Patients were categorized, according to HPV L1 protein sequence homology, into the HPV α-9 (HPV 16, 31, 33, 52, and 58), HPV α-7 (HPV 18, 39, 45, 59, and 68) or 'other' (HPV 51 and 56) groups. Associations between HPV genotype and clinical outcome following RT were evaluated. A total of 54 (65.1%) tumors were HPV α-9-positive, 13 (15.7%) were HPV α-7-positive, 2 (2.4%) were categorized under 'other' and 14 (16.9%) were HPV-negative. There were no significant differences in age, FIGO stage, regional lymph node metastases rate at diagnosis, or concurrent chemotherapy administration between the HPV α-9 and α-7 groups. The median follow-up period was 52 months (range, 2-156 months). The 5-year disease-free survival rates were 54.5 and 30.8% in the HPV α-9 and α-7 groups, respectively (P=0.034), and the 5-year distant metastasis rates were 38.0 and 69.2%, respectively (P=0.015). There were no significant differences in the 5-year local control or overall survival (OS) rates between the two groups. HPV genotype affected the 5-year distant metastatic rate, however not the 5-year local control or OS rate in patients with uterine cervical cancer following RT.